2007
DOI: 10.1111/j.1469-8749.2007.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a static bicycling programme on the functional ability of young people with cerebral palsy who are non‐ambulant

Abstract: This study investigated the effects of exercise on the motor function of 11 young people (10 females, one male; age range 11-15y; mean age 12y 7mo [SD 1y 4mo]) with cerebral palsy (CP) who were non-ambulant (Gross Motor Function Classification System Levels IV or V), using an adapted static bicycle. Three participants had dyskinetic quadriplegia, seven had spastic quadriplegia, and one had spastic diplegia. The study used an ABA design with participants acting as their own controls with 6-week baseline, 6-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 22 publications
3
74
0
Order By: Relevance
“…Therefore, cycling-based movement is often used for walking training as well as the lower limb coordination training [11]. Previous research in literature even indicates that patients with stroke and cerebral palsy may improve their motor and balance abilities after an early short duration of cycling training [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cycling-based movement is often used for walking training as well as the lower limb coordination training [11]. Previous research in literature even indicates that patients with stroke and cerebral palsy may improve their motor and balance abilities after an early short duration of cycling training [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Test items within both dimensions (transitioning from high kneeling to standing, unilateral stance, stepping, jumping, and hopping) improved and were consistent with gains in knee extensor strength. Williams and Pountney (2007) found a greater increase on the GMFM (mean = 7.3% increase, p < .05) following a stationary cycling intervention for 11 non-ambulatory children with CP. They attributed the large gain to pre-existing low levels of functional ability and few opportunities to participate in physical activity.…”
Section: Discussionmentioning
confidence: 79%
“…Research has shown that children with CP can cycle independently but demonstrate differences in muscle recruitment patterns (Johnston, Barr, & Lee, 2007;Kaplan, 1995), joint kinematics (Johnston et al, 2007), and pedal forces (Johnston, Prosser, & Lee, 2008), compared to children without CP. A recent study showed that stationary cycling could be an effective intervention for children with CP, even those who are non-ambulatory (Williams & Pountney, 2007). After a six-week, three times weekly stationary cycling intervention, these children demonstrated improved supported standing, cruising, and stepping on the Gross Motor Function Measure (GMFM) (p = 0.01).…”
Section: Stationary Cycling As An Interventionmentioning
confidence: 99%
“…Previous studies have found that pedaling improved physical endurance as a result of improving oxygen consumption, gross motor function and oxygen uptake but none of these studies recorded an improvement in walking speed. A previous study applied on 70 ambulatory children with spina bifida reported an improvement in walking speed and step length after 4 weeks of repetitive ergometer training [18,19].…”
Section: Discussionmentioning
confidence: 99%